A Randomized Clinical Trial of Prophylactic Effects of Vitamin D on Different Indices of Osteopenia of Prematurity - P Alizadeh; F Naderi; K Sotoudeh (Tehran University of Medical Sciences, 2006)
Prevention and treatment of the rickets of prematurity is an important aspect of the care of preterm infants. The purpose of this study was to compare the prophylactic effects of different doses of vitamin D on the clinical, biochemical and radiological indices of the rickets of prematurity. In a randomized clinical trial, 68 premature infants (